Older Adult Education: A New Site for Colonization? - Brian Findsen (Adult Education Research Conference, 2011)
This paper argues that conventional older adult education has been captured largely by the white middle class and that social justice imperatives are missing. This form of education has been colonized by a significant minority to the detriment of a liberating agenda for many older adults.